Interleaved configurations of percutaneous epidural stimulation enhanced overground stepping in a person with chronic paraplegia - Gorgey, Ashraf S.; Venigalla, Siddharth; Rehman, Muhammad Uzair; George, Botros; Rejc, Enrico; Gouda, Jan J. (Frontiers in Neuroscience, 2023)
Descending motor signals are disrupted after complete spinal cord injury (SCI) resulting in loss of standing and walking. We previously restored standing and trunk control in a person with a T3 complete SCI following implantation of percutaneous spinal cord epidural stimulation (SCES). We, hereby, present a step-by-step procedure on configuring the SCES leads to initiate rhythmic lower limb activation (rhythmic-SCES) resulting in independent overground stepping in parallel bars and using a standard walker. Initially, SCES was examined in supine lying at 2 Hz before initiating stepping-like activity in parallel bars using 20 or 30 Hz; however, single lead configuration (+2, -5) resulted in lower limb adduction and crossing of limbs, impairing the initiation of overground stepping. After 6 months, interleaving the original rhythmic-SCES with an additional configuration (-12, +15) on the opposite lead, resulted in a decrease of the extensive adduction tone and allowed the participant to initiate overground stepping up to 16 consecutive steps. The current paradigm suggests that interleaving two rhythmic-SCES configurations may improve the excitability of the spinal circuitry to better interpret the residual descending supraspinal signals with the ascending proprioceptive inputs, resulting in a steppinglike motor behavior after complete SCI.